Characterization of fracture behavior of concrete structural elements using acoustic emission technique / Arash Behnia - Behnia, Arash (2015)
In this study, basically, acoustic emission technique was applied to develop its application in concrete structural members. Four different types of experimental sets were conducted to study the structural concrete members fracture and condition monitoring. The first experiment set was carried out for pure torsion fracture analysis to characterize fracture parameters under pure torsion by means of acoustic emission incorporated with statistical approach (Weibull method). As a first study, the damage Weibull parameters for torsional fracture were calibrated by acoustic emission so that damage probability function was proposed. In the next study, a pattern recognition technique, kernel fuzzy c-means (KFCM), was applied to cluster different damage stages so that a novel damage index called spatial intelligent b-value was proposed to quantify damage in an unsupervised approach. Thereafter, the second experiment was conducted for large scales multi-cells beams subjected to pure torsional loading. The fracture process was qualitatively and qualitatively characterized by means of AE analysis. The third set of experiment aims to study the concrete slab fracture behaviour and provide early warning of occurrence of damage whist the type of failure can be characterized by means of AE. AE could quantify stiffness reduction in composite slabs under concentrated loading other than offering an early warning system. In the next step, by means of statistical process control and autoregressive method a novel structural health monitoring scheme was proposed to detect damage and analyse reliability of failure in composite slabs. The last experiments utilized fiber reinforced concrete beams subjected to flexural loading to investigate the combination of AE with travel time tomography technique to provide a robust global and local technique. Innovatively, global and local structural condition could be evaluated by integration acoustic emission signal strength and velocity of time tomography in a combined plot.